Sosyal Medyada Yer Alan Haberlerin Ve Olumsuz Paylaşımların İş Tatmini Üzerine Etkisi: Türkiye'de Alan Araştırması - Debbik, Khalid Salim (Zenodo, 2024)
This study aims to examine the potential effects of news published on social media on employees' job satisfaction. The research acknowledges the increasing impact of social media in daily life and its influence on individuals' access to information related to their jobs. However, the clear impact of social media on job satisfaction remains uncertain. Therefore, this study aims to conduct a field research to understand the potential effects of news published on social media on employees' job satisfaction. The participants of the study consist of 50 individuals from different sectors and diverse socio-economic backgrounds. During the data collection process, participants were evaluated using a 10-question interview set, which included their opinions on news present on social media, their levels of job satisfaction, and their experiences in the workplace. The findings indicate that news present on social media has a complex impact on job satisfaction. Some participants mentioned that accessing current information related to their jobs through social media increased their job satisfaction positively, while others expressed that these news sources increased job stress and consequently decreased job satisfaction. These conflicting results deepen our understanding of how social media is perceived and utilized in the workplace. In conclusion, this study emphasizes the necessity for further research to understand the effects of social media on job satisfaction..
Keywords: 8. Economic growth; 16. Peace & justice